The geo-politics of genetic modified organisms - Kneen, Brewster (Universidad Nacional de Quilmes, 2002)
The dismantling of national sovereignty and social integrity, the deliberate and systematic violation of any and all boundaries, and the systematic violation of the integrity of organisms are the hallmarks of globalization as well as genetic engineering. This is the context in which the deepening integration of Argentina and Brazil into the global corporate operations of Monsanto and Cargill, from the molecular to the national level, are analyzed here using the example of soya. After selling its global seeds business to Monsanto in 1988, the two companies then formed a joint venture, Renessen, "in the first global alliance that spans the agricultural value chain." Nature responds to such efforts to control and profit through a globalized monoculture (and oligopoly) with mutations and adaptations that produce a diversity of biological mechanisms to overcome such assaults. Therein lies our hope and example.